Development of a Basic Professional Educational Programs for Teacher Training according to Teacher Professional Standart - Akhtarieva R.F. (Психологическая наука и образование (2007. Online), 2015)
A teaching position involves professional activities in keeping with professional standards, as well as competences and knowledge necessary for it. Development of a basic professional educational program improves teacher training to make it more practice-oriented, so the ability of the future teacher to act according to the professional standard becomes basic educational result. The article describes the features of our basic professional educational program for teaching training, developed according to professional standards and peculiarities of professional activity. The basic professional program consists of modules developed in the light of idea of “eventness” when Incoming or Outcoming Event means the level of ability to professional performance.